Pengembangan Aplikasi Multimedia untuk Pembelajaran Satelit Astronomi NASA dengan Teknologi Augmented Reality Berbasis Android - Dilan Arya Sujati; R. Rizal Isnanto; Kurniawan Teguh Martono (Jurnal Teknologi dan Sistem Komputer, 2016)
With the advancement of technology in various aspects of life of today's technology allows developers to create applications that aims to facilitate the public in obtaining information based on mobile. Seeing the importance of the role of astronomy satellites it needs to make a multimedia application with Augmented Reality technology that can provide an overview and brief specifications on astronomy satellite without having to go to the planetarium or observatory.This research is using MDLC (Multimedia Development Life Cycle) framework. The process of assembly (pemasangan) was performed using Unity and Vuforia library. The result is a book containing related image about NASA’s astronomy satellites which functioned as a marker and an Augmented Reality application based on Android that is capable of displaying NASA’s astronomical satellites on the top of marker that can display brief information about the shape and its parts when touched on the screen. The application that has been made function properly and in accordance with the concept and design. The ideal condition of using the application in places exposed to light with the intensity of 108,3 ± 2,5 lux upwards. In addition the camera is directed to the distance between 10-75 cm of the marker and the angle between 40 ± 0,5 O – 140 ± 0,5 O .. The greater the intensity of the light does not affect the sensitivity of the camera to detect the marker increases. In other words, the marker will not be detected if the distance marker on the camera more than 75 cm and the angle of the camera marker less than 40 ± 0,5 O or more than 140 ± 0,5 O though the light intensity is greater.